FAULT SYSTEM TO COMPENSATE THE DAMAGE CAUSED TO PATIENTS - Morkūnaitė, Monika (Teisė, 2017)
This article highlights that there are many systems designed to compensate damages caused to patients by improper health care delivery. However, there is no agreement which of these systems proposes the best solution to compensate damages caused to patients and is the most suitable to ensure their safety. In Lithuania, the fault system is implemented for such compensations, meaning that questions of medical liability are solved through an application of a civil liability in the court system. Existing medical malpractice liability system has two principal objectives: firstly, to compensate patients who are injured through the negligence of healthcare providers, secondly, to deter health care providers from practising negligently. However, in Lithuania, there are some initiatives to implement a no-fault system, arguing that a fault system is ineffective to compensate caused damages; moreover, systemic errors in the system are not identified and later – prevented. Thus, in this article the conceptual issues of application of a fault system are analysed. It suggests that a fault system has advantages and disadvantages. In order to receive a compensation a patient has to file a claim in court where all civil liability conditions are evaluated. Such dispute resolution practice provides incentives to ensure a proper health care delivery, but to some extend it contributes to practising defensive medicine and non identification of systemic errors in health care delivery. The article concludes that fault system is not per se ineffective and measures to minimise these negative aspects can be taken.